Development of Augmented Reality-Based Flashcard Media "Oreng Madureh" as an Introduction to Madurese Culture - Rachmawati, Ita; Karim, Muhammad Busyro; Nisa, Titin Faridatun (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2023)
The development of augmented reality (AR) based flashcard media "Oreng Madureh" has the potential to become an effective and interesting educational and cultural promotion tool with a combination of AR and Madurese culture. This research aims to develop learning media using AR-based flashcard media on introductory Madurese culture material which includes an introduction to traditional clothing, typical food and Madurese traditional houses. This development research uses the ADDIE model which consists of five stages, namely analysis, design, development, implementation and evaluation. Data collection used observation, questionnaires, interviews and documentation techniques for 50 children aged 4-6 years in 4 trial stages, namely material expert trials, learning media experts, small group and large group field trials. The data was analyzed quantitatively and qualitatively with material expert questionnaire trial results of 91.07%, learning media expert trial results of 92.64% with very feasible criteria, no need for revision, small group trial results of 87.14% and the results of the large group trial were 84.89% in the high category. These results indicate that this media is suitable for use in the learning process. The development of this media has the implication of being able to attract children to understand and appreciate the cultural diversity around them through interactive learning activities, as well as developing children's fine motor and cognitive skills.